2009
DOI: 10.1519/jsc.0b013e31819b78c4
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness Qualities of Professional Volleyball Players: Determination of Positional Differences

Abstract: The purpose of this study was to investigate the anthropometric and strength characteristics of elite male volleyball athletes and to determine if differences exist in these characteristics according to playing position. A group of 35 professional male team volleyball players (mean +/- SD age: 26.6 +/- 3.1 years) participated in the study. Players were categorized according to playing position and role: middle blockers (n = 9), opposite hitters (n = 6), outside hitters (n = 10), setters (n = 6), and liberos (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
83
2
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 8 publications
11
83
2
8
Order By: Relevance
“…Moreover, there are no studies that determine the eff ect of volleyball training on non-athletic university students. Th is is of interest as volleyball is a competitive sport that relies mainly on explosive strength and endurance to perform techniques such as blocking and smashing (Marques, van den Tillaar, Gabbett, Reis, & González-Badillo, 2009). Th us, the aim of this study was to determine the eff ect of a volleyball course on the health-related fi tness of male university students.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are no studies that determine the eff ect of volleyball training on non-athletic university students. Th is is of interest as volleyball is a competitive sport that relies mainly on explosive strength and endurance to perform techniques such as blocking and smashing (Marques, van den Tillaar, Gabbett, Reis, & González-Badillo, 2009). Th us, the aim of this study was to determine the eff ect of a volleyball course on the health-related fi tness of male university students.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need of high level of physical and physiological fitness to participate at the elite level (Marques et al, 2009). Training can improve the performance of the players (Bompa, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Specific characteristics such as height are considered to be essential to achieve high performance in volleyball 4 . In addition to knowledge about the specific profile of each sport modality, the rapid advances in elite sports require professionals to understand the specific physical characteristics in different playing positions or functions within the same modality in an attempt to increase training efficiency and to provide better specific training guidance 5 . Within this context, somatotype analysis adds information to common anthropometric measures (height, body weight, skinfolds, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have used somatotype analysis to establish the ideal physical profile of volleyball players in each playing position in order to facilitate training programs 3,6,11,12 . Studies regarding somatotype in volleyball conducted in different countries concluded that teams of the same category and qualification level tend to present a similar somatotype profile, whereas other studies found in the same category homogeneity of the somatotype profile in different playing positions for both male and female athletes 5,11,[13][14][15] . Studies on Brazilian volleyball have classified the somatotype of female athletes into levels of trainings 16 , as well as of the Brazilian under-17 male team 15, .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation